FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN RESIKO TINGGI DALAM KEHAMILAN PADA IBU HAMIL DI PUSKESMAS SUNGAI PANAS KOTA BATAM TAHUN 2017 - Hartati, Nurita; Mariyana, Mariyana (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2018)
Maternal Mortality Rate (MMR) is associated to pregnancy and childbirth which considered very high to happen. The purpose of this study is to determine the factors associated with high risk pregnancy on prenatal women at Sungai Panas Health Centre of Batam City in 2017. This research is a descriptive analytic study with retrospective approach using the medical record with checklist sheetas the secondary data. This study was conducted in June 2017 with 54 respondents selected through purposive sampling method. The data is analyzed using Chi-Square test. From the result of the research, it is found that31 respondents (57,4%) aged 20-35 years old, besides, the number of labor given by the 50 postpartum mothers (92,6%) is<5,49 mothers (90.7%) give the gap between the pregnancy > 2 to 5 years period, 32 of them (59.3%) with upper arm circumference (LILA) are not at risk for low energy chronic (KEK) â‰¥ 23.5. The Chi Square result then summaries that there is a correlation between maternal age and upper arm circumference (LILA) with high risk of pregnancy with p = 0.000, nevertheless, there is no correlation between the number of the laboring process of mothers, pregnancy distance with the high risk pregnancy with p = 1.000. At last, it is expected that SeiPanasHealth Centre to be able to improve their midwifery services by implementing KIE (Communication, Information and Education) to prenatal women to diminish high risk during pregnancy as well asin childbirth.Â